Analysis of aquatic insects’ communities of Awba reservoir and its physico-chemical properties (2011)
This study was conducted to assess the Awba reservoir insects’ communities and the health status through the determination of insects’ abundance, composition, distribution and water qualities parameters. Water samples and insects were collected bi-weekly from August through December, 2009. Insects were sampled using standard entomological methods, while water samples was analyzed using standard Winkler’s titrimetric and APHA methods to determine the chemical properties. Water analyses and insects’ identifications were conducted in the laboratory in Department of Zoology, University of Ibadan, Oyo State. The results show that only DO and phosphate-phosphorus had significant difference (p<0.05). A total of 1,154 insects were recorded, Chironomidae and Culicidae were most abundance. The chemical properties and the distinct taxa found in the water suggest that the water body is polluted and may be dangerous to the health of people around the reservoir.